Automated Generation and Evaluation of JMH Microbenchmark Suites From Unit Tests - Jangali, Mostafa; Tang, Yiming; Alexandersson, Niclas; Leitner, Philipp; Yang, Jinqiu; Shang, Weiyi (IEEE transactions on software engineering, 2023)
Performance is a crucial non-functional requirement of many software systems. Despite the widespread use of performance testing, developers still struggle to construct and evaluate the quality of performance tests. To address these two major challenges, we implement a framework, dubbed ju2jmh , to automatically generate performance microbenchmarks from JUnit tests and use mutation testing to study the quality of generated microbenchmarks. Specifically, we compare our ju2jmh generated benchmarks to manually written JMH benchmarks and to automatically generated JMH benchmarks using the AutoJMH framework, as well as directly measuring system performance with JUnit tests. For this purpose, we have conducted a study on three subjects ( Rxjava , Eclipse-collections , and Zipkin ) with \sim ∼<inline-graphic xlink:href="tang-ieq1-3188005.gif"/> 454K source lines of code (SLOC), 2,417 JMH benchmarks (including manually written and generated AutoJMH benchmarks) and 35,084 JUnit tests. Our results show that the ju2jmh generated JMH benchmarks consistently outperform using the execution time and throughput of JUnit tests as a proxy of performance and JMH benchmarks automatically generated using the AutoJMH framework while being comparable to JMH benchmarks manually written by developers in terms of tests' stability and ability to detect performance bugs. Nevertheless, ju2jmh benchmarks are able to cover more of the software applications than manually written JMH benchmarks during the microbenchmark execution. Furthermore, ju2jmh benchmarks are generated automatically, while manually written JMH benchmarks require many hours of hard work and attention; therefore our study can reduce developers' effort to construct microbenchmarks. In addition, we identify three factors (too low test workload, unstable tests and limited mutant coverage) that affect a benchmark's ability to detect performance bugs. To the best of our knowledge, this is the first study aimed at assisting developers in fully automated microbenchmark creation and assessing microbenchmark quality for performance testing.